PELAKSANAAN LELANG TERHADAP KREDIT MACET PADA PT. BANK RAKYAT INDONESIA (PERSERO) CABANG DUMAI - Ariyana Rezki Ananda; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Bank according to Article 1 paragraph 2 of Law No. 10 of 1998 concerning Amendment to Law Number 7 of 1992 concerning Banking, "the bank is an entity that collects funds from the public in the form of savings and channel them to the public in the form of credit or other forms in order to improve the living standards of the people. "Based on this, the bank conducting credit to debtors who need funding for business or production activities. Based on the principle of prudence of banks in providing credit, the bank noticed collateral for a loan. The credit guarantee essentially serves to ensure the certainty of repayment of the debtor if the debtor in default or bankruptcy.Under Article 6 of Law Encumbrance, if the debtor injury appointment or default, the first mortgage holder of the right has the right to sell the object of encumbrance on its own power through public auction. Repayment of the receivable is taken of the results of the auction. This is what is commonly called parate execution. This formulation also contained in Article 1 178 Paragraph (2) of the Civil Code. However, before the bank was trying to rescue a credit according to Bank Indonesia Circular Letter No. 23/12 / BPPP dated February 28, 1991, namely Rescheduling, Reconditioning, Restructuring.Definition of an auction pursuant to Article 1 of the Minister of Finance Regulation No. 40 / PMK.07 / 2006 on Guidelines for the Implementation of the Auction, the auction is a sale of goods which is open to the public at a price quote in writing and / or oral increased or decreased to achieve the highest price preceded by the announcement of the auction.The auction is expected to restore the banks' losses on customer receivables of the debtor. However, changes to the object at auction guarantees that would result in losses for banks, namely the declining price of the auction object. As a result, bank losses due to auction proceeds do not cover the debts that are overdue. Because the auction results do not meet the debt, the bank asks the customer accountability to creditors.Keywords : Implementation-Auction-Bad Credit-Guanrantee